Etika sebagai Landasan Moral Pengembangan Kelembagaan Ekonomi - Noer Soetrisno (Universitas Islam Indonesia, 2004)
If economical crisis that emerged at the end of 1990s became a basis of introspect toward the long journey and development of Indonesian economy is reason enough. After Indonesia economy had high growth that supported with aggregated number developing. Unfortunately, the development and the prestige of Indonesian economy that mentioned above suddenly it declined till it needs to be repaired in particular it needs reorienting economical policy in Indonesia. According to the writer of article that the solution of the problem is to elaborate ethical and moral value to develop economical institution, individual and government.